2004
DOI: 10.1002/glia.20048
|View full text |Cite
|
Sign up to set email alerts
|

Activation of P2 nucleotide receptors stimulates acid efflux from astrocytes

Abstract: Acidification of the extracellular fluid modulates neurotransmission and ischemic injury in brain. The purpose of the present study was to investigate the effects of purine and pyrimidine transmitters on acid efflux from brain astrocytes. Using RT-PCR, we detected transcripts for the following nucleotide receptors in rat primary astrocyte cultures: P2X1, P2X2, P2X3, P2X4, P2X6, P2X7, P2Y1, P2Y2, P2Y4, and P2Y6. Adenosine 5'-triphosphate (ATP) was found to rapidly induce a biphasic increase in acid efflux, moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 74 publications
3
23
0
Order By: Relevance
“…As shown by our in vitro results, LPS-induced IL-6 production is probably mediated by an effect of ATP on other purinergic receptors than P2X 7 R. Both microglia and astrocytes are important sources of IL-6 (Lee et al, 1993;van Wagoner and Benveniste, 1999). As both microglia and astrocytes express TLR4 (Bowman et al, 2003;Chakravarty and Herkenham, 2005) and P2Y receptors (Dixon et al, 2004;Franke et al, 2004;Fumagalli et al, 2003;Yamakuni et al, 2002) it is therefore possible that LPS as well as other inflammatory cytokines directly trigger IL-6 release by these cells independently of IL-1β.…”
Section: Discussionsupporting
confidence: 55%
“…As shown by our in vitro results, LPS-induced IL-6 production is probably mediated by an effect of ATP on other purinergic receptors than P2X 7 R. Both microglia and astrocytes are important sources of IL-6 (Lee et al, 1993;van Wagoner and Benveniste, 1999). As both microglia and astrocytes express TLR4 (Bowman et al, 2003;Chakravarty and Herkenham, 2005) and P2Y receptors (Dixon et al, 2004;Franke et al, 2004;Fumagalli et al, 2003;Yamakuni et al, 2002) it is therefore possible that LPS as well as other inflammatory cytokines directly trigger IL-6 release by these cells independently of IL-1β.…”
Section: Discussionsupporting
confidence: 55%
“…Second, the ability of NHERF proteins to interact with PKC (25) might facilitate the tethering of PKC in the vicinity of P2Y 1 R and thereby modulate the ability of PKC to phosphorylate and regulate the activity of P2Y 1 R (17). Third, NHERF-2 is known to regulate the activity of Na ϩ ͞H ϩ exchangers (37) and therefore may play a role in linking P2Y 1 R to modulation of Na ϩ ͞H ϩ exchange (38). Finally, it is interesting to note that NHERF-2 has been shown to form a high-affinity complex with the cystic fibrosis transmembrane regulator (CFTR) in A6 cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition several studies report the presence of mRNA encoding P2 receptors in astrocytes cultured from rodent brain. While the extent of analysis varies between studies, mRNAs for all subtypes of P2Y and P2X receptors have been reported [37,38]. The presence of mRNA does not prove the presence of functional protein.…”
Section: Discussionmentioning
confidence: 99%